2019
DOI: 10.1016/j.yebeh.2018.11.016
|View full text |Cite
|
Sign up to set email alerts
|

The refractory epilepsy screening tool for Lennox–Gastaut syndrome (REST-LGS)

Abstract: Background: The complex clinical presentation and progression of Lennox-Gastaut syndrome (LGS) can complicate the accurate diagnosis of this severe, lifelong, childhood-onset epilepsy, often resulting in suboptimal treatment. The Refractory Epilepsy Screening Tool for LGS (REST-LGS) was developed to improve the identification of patients with LGS. Methods: Using the Modified Delphi Consensus, a group of experts developed and tested the REST-LGS Case Report Form (CRF) comprising 8 criteria (4 major, 4 minor) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Similarly, the cross‐sectional nature of this medical record data will compound this. The evolving EEG and phenotypic features often seen in LGS may contribute to failure to capture key criteria at the time of review, 4 , 13 , 14 especially in patients with a longer duration of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the cross‐sectional nature of this medical record data will compound this. The evolving EEG and phenotypic features often seen in LGS may contribute to failure to capture key criteria at the time of review, 4 , 13 , 14 especially in patients with a longer duration of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…However, these patients were not statistically significantly older. It has been previously reported that both seizure types and SSW discharges may reduce in frequency over time, 3 , 13 , 14 , 16 potentially making them less likely to be reported in patients living with LGS for longer. Our limited analysis may suggest that the reported evolution of phenotypic and electroclinical features in LGS are more dependent on disease progression than patient age.…”
Section: Discussionmentioning
confidence: 99%
“…The REST-LGS was designed using the Modified Delphi Consensus approach, a rigorous method in which available scientific evidence and collective judgment of a group of experts (including epileptologists, advanced practice nurses trained in epilepsy, neurology residents, and scientists) were combined to develop the screening tool. 13 The REST-LGS consists of 8 criteria - answer for all 4 major criteria is considered "Definite LGS". 13 The majority of patients with confirmed LGS in the original REST-LGS validation study exhibited 3 major criteria and 2 to 3 minor criteria, suggesting that meeting these thresholds would be indicative of LGS.…”
Section: Rest-lgs Questionnairementioning
confidence: 99%
“…13 The REST-LGS consists of 8 criteria - answer for all 4 major criteria is considered "Definite LGS". 13 The majority of patients with confirmed LGS in the original REST-LGS validation study exhibited 3 major criteria and 2 to 3 minor criteria, suggesting that meeting these thresholds would be indicative of LGS.…”
Section: Rest-lgs Questionnairementioning
confidence: 99%
See 1 more Smart Citation